Decision Support System for Teacher Competency Evaluation Using Profile Matching and Rule-Based Coaching - Siti Nuraida Mangunsong; Rizaldi Rizaldi; Nurul Rahmadani (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
Teacher competency evaluation plays a crucial role in improving educational quality; however, assessment practices at MTSS MPI Bagan Asahan are still conducted manually, leading to limited documentation, potential subjectivity, and the absence of systematic analysis. This study aims to develop a Decision Support System (DSS) based on the Modified Profile Matching method to measure teacher competency alignment with predefined ideal standards and generate proportional coaching recommendations. A quantitative case study was conducted involving 22 active teachers selected through total sampling. Data were collected from supervision documents, observations, interviews, and literature review. Competency evaluation was performed using GAP analysis between actual and target profiles, applying a 60% weighting for Core Factors and 40% for Secondary Factors to compute final ranking scores. The results show that competency scores ranged from 3.80 to 4.70, with a mean of 4.25 and a standard deviation of 0.24, indicating relatively homogeneous performance levels. Beyond ranking, the system generates adaptive coaching recommendations based on the number of negative GAP indicators. Black Box testing confirms functional reliability. The integration of proportional rule-based recommendations transforms the DSS from a static ranking tool into a structured competency diagnostic and professional development planning system. The proposed system also has the potential to be implemented in other educational institutions to support objective and data-driven teacher competency evaluation.